The Dark Side of School Culture - Patricia Mannix-McNamara; Niamh Hickey; Sarah MacCurtain; Nicolaas Blom (Societies, 2021)
The extant literature evidences the link between incivility and workplace culture. Both have a symbiotic relationship whereby a change in one influences the other. When workplace cultures develop dysfunctional values and beliefs, negative traditions, and caustic ways of interacting, they have become “toxic cultures.” This study examined Irish post-primary school teachers’ experiences of incivility and toxic culture in the workplace through in-depth interviews with forty-two participants. Results show that toxic work culture had a negative impact on both the personal and professional lives of the participants. We conclude that antecedents in toxic school culture are linked to epistemological assumptions, group dynamics, and deficiencies in leadership, and we suggest that they act as causes and/or facilitators of workplace bullying.